2017
DOI: 10.1016/j.preghy.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study to assess changes in arterial stiffness and cardiac output parameters among low-risk pregnant women

Abstract: The current study provides pregnancy normograms for gestational changes in arterial stiffness and cardiac output parameters among low-risk, healthy pregnant women. Further work will be required to assess the risk of placental mediated diseases and pregnancy outcome among pregnant women with parameters outside the normal range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
5
17
1
Order By: Relevance
“…Pregnancy is a unique physiologic model showing that morphologic, hemodynamic, and functional adaptation of the heart in the transient preload and afterload changes. Increasing the volumetric load and decreasing peripheral resistance during pregnancy have been well documented in previous publications . The increase in the volume load in the third trimester worsens potential heart disease.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Pregnancy is a unique physiologic model showing that morphologic, hemodynamic, and functional adaptation of the heart in the transient preload and afterload changes. Increasing the volumetric load and decreasing peripheral resistance during pregnancy have been well documented in previous publications . The increase in the volume load in the third trimester worsens potential heart disease.…”
mentioning
confidence: 52%
“…Increasing the volumetric load and decreasing peripheral resistance during pregnancy have been well documented in previous publications. 1,2 The increase in the volume load in the third trimester worsens potential heart disease. Previous studies demonstrated changes in left ventricular (LV) function during pregnancy, particularly diastolic function.…”
mentioning
confidence: 99%
“…A plausible physiological candidate for predicting the likelihood of hypotension in C/S patients undergoing spinal anesthesia is arterial stiffness (AS), which has been investigated in the separate contexts of hypotension and pregnancy, and can be assessed using pulse contour analysis [12]. Recent work on the prediction of imminent hypotension has focused on identifying changes in the variability of physiological signals, among them AS [13,14]. Variability changes are due to compensatory mechanisms in the cardiovascular system as it attempts to maintain stability [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…Variability changes are due to compensatory mechanisms in the cardiovascular system as it attempts to maintain stability [10,15]. In the context of pregnancy, significant longitudinal changes in AS have been documented [13]. It is therefore reasonable to investigate whether underlying compromised physiological compensatory reserve can be predicted prior to spinal anesthesia induction.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy is associated with significant changes in maternal haemodynamics and measures of arterial stiffness across each trimester (1). In particular, significant increases in arterial stiffness and wave reflection parameters are noted amongst pregnant women who subsequently develop pre-eclampsia and small for gestational age foetuses (2), as well as those with known pre-eclampsia (3).…”
Section: Introductionmentioning
confidence: 99%